Qatar : Selected Issues. - International Monetary Fund. Middle East and Central Asia Dept. (Washington, D.C. : International Monetary Fund, 2013)
Qatar has recently taken steps toward introducing a medium-term budget framework (MTBF) to enhance the predictability of spending decisions in the country. However, implementing medium-term fiscal planning requires formal procedural fiscal rules and parallel efforts to enhance the credibility of the annual budget. Given Qatar's significant exposure to hydrocarbon price movements and its long-lasting hydrocarbon reserves, such fiscal rules would need a certain degree of flexibility and, at the same time, should be set to maintain consistency with long-term fiscal sustainability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet